More than Just Contrarians: Insider Trading in Glamour and Value Firms. (6th June 2011) - Gregory, Alan; Tharyan, Rajesh; Tonks, Ian
Abstract: This study examines the patterns of, and long‐run returns to, directors' (insiders') trades along the value‐glamour continuum in all stocks listed on the main London Stock Exchange and analyses what these directors' trades add to a naïve value‐glamour strategy. We consider alternative definitions of value in defining trades and in the construction of our benchmark portfolios so that directors' trades are evaluated net of any value‐glamour effect, variously defined. We find that directors consistently trade in a contrarian fashion, buying more value stocks and selling more glamour stocks, with purchases following price falls and sales following price rises. Directors' buy signals in value stocks generate significant positive abnormal returns while the sell signals in glamour stocks generate smaller and generally insignificant negative returns. In contrast to the results from US studies, we find that the positive abnormal returns in value stocks persist for up to two‐years after the initial directors' trading signal. Abnormal returns are particularly concentrated in smaller value stocks, and are robust to alternative definitions of value .